TINGKAT BERPIKIR MAHASISWA PADA MATA KULIAH GEOMETRI DITINJAU DARI GAYA KOGNITIF - Exacta, Annisa Prima; Hadiprasetyo, Krisdianto (Journal of Mathematics and Mathematics Education, 2018)
Abstract: Differences in cognitive styles influence students’ mindset and behavior. Students with Field Independent (FI) cognitive style have different mindset with Field Dependent (FD) students. By identifying cognitive style, lecturer needs to understand the concept of material due to the way in explaining it to students. The objectives of this study are to find out: (1) students’ thinking level in Geometry who have Field Dependent (FD) cognitive style, (2) students’ thinking level in Geometry who have Field Independent (FI) cognitive style. This research is conducted at Teacher Training and Education Faculty of Veteran Bangun Nusantara Sukoharjo in Mathematics Education Department in the academic year of 2017/2018. It is a qualitative descriptive research. Data about thinking levels are obtained from diagnostic tests and interview results, while data on cognitive style are obtained from the results of Group Embedded Figure test (GEFT). Subjects are taken by purposive sampling technique and triangulation method is used as data validation. In analyzing data, the researchers employ some stages consisting of data reduction, data presentation, and conclusion. The results reveal that students’ thinking level who have Field Dependent (FD) cognitive style in Geometry course is visualization and pre-analysis, while students’ thinking level who have of Field Independent (FI) cognitive style in Geometry course is visualization, analysis, and informal pre-deduction.Keywords:Thinking Level, Cognitive Style, Field Independent (FI), Field Dependent (FD), Geometry.